Changes in Soil Aggregates and Aggregate-Associated Carbon Following Green Manure–Maize Rotations in Coastal Saline Soil - Yinjuan Li; Xuxia Jia; Weiliang Zhao; Richu Gao; Wan Luo; Tongshun Wang (Agronomy, 2025)
Coastal saline–alkali soils, characterized by poor structures and low fertility, limit sustainable agricultural development. This study aimed to investigate how green manure application influence soil aggregate stability and soil organic carbon (SOC) sequestration in such coastal saline soils. Field experiments were conducted by comparing the following five treatments: (1) control (CK); (2) ryegrass full incorporation (RF); (3) ryegrass mulching (RM); (4) alfalfa full incorporation (AF); (5) alfalfa mulching (AM). The results demonstrated that green manure application significantly increased large macroaggregate (>2 mm) proportions by 20.60–56.70% while reducing microaggregates (<0.25 mm) by 24.35–68.43%. SOC increased across 0–40 cm soil depth, primarily driven by large macroaggregates and microaggregates, which contributed 23.7–73.5% and 34.8–91.4% of the total increase, respectively. Mulching treatments (AM/RM) increased surface SOC sequestration, while full-incorporation practices (AF/RF) boosted subsoil SOC stocks. These results highlight green manure application as an effective strategy to rehabilitate coastal saline soils by enhancing aggregate stability and SOC sequestration, providing technical guidance for saline soil rehabilitation in coastal saline regions.